1 Corinthians an introduction and commentary - Schreiner, Thomas R. 1954- (La Vergne IVP, 2018)
Intro -- To Tom Reilly and Randon Wickman, dear and beloved friends for almost fifty years now -- GENERAL PREFACE -- AUTHOR'S PREFACE -- ABBREVIATIONS -- General -- Ancient texts -- Bible versions -- SELECT BIBLIOGRAPHY -- Commentaries on 1 Corinthians -- Other commentaries, books, monographs and articles -- INTRODUCTION -- 1. The city of Corinth -- 2. Paul and Corinth -- 3. The occasion for the letter -- 4. The nature of the letter -- 5. Major theological themes -- ANALYSIS -- COMMENTARY -- 1. INTRODUCTION (1:1-9) -- A. Greeting (1:1-3) -- B. Thanksgiving (1:4-9) -- 2. ADDRESSING PROBLEMS IN THE CHURCH (1:10 - 6:20) -- A. Exhortation for church unity (1:10 - 4:21) -- B. Problems of church purity (5:1 - 6:20) -- 3. ANSWERS TO CONTEMPORARY ISSUES IN THE CHURCH (7:1 - 16:4) -- A. Marriage matters (7:1-24) -- B. Instructions about virgins (7:25-40) -- C. Idol food: edification and danger (8:1 - 11:1) -- D. Order and worship (11:2-34) -- E. Spiritual gifts (12:1 - 14:40) -- F. The resurrection (15:1-58) -- G. Collection for the believers in Jerusalem (16:1-4) -- 4. CONCLUSION (16:5-24) -- A. Travel plans (16:5-9) -- B. Timothy and Apollos (16:10-12) -- C. Exhortations (16:13-18) -- D. Greetings (16:19-21) -- E. A warning, grace and love (16:22-24) -- NOTES.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Kommentar